Kinematics and spatiotemporal parameters of infant‐carrying in olive baboons. Issue 3 (25th July 2014) - Anvari, Zohreh; Berillon, Gilles; Asgari Khaneghah, Asghar; Grimaud‐Herve, Dominique; Moulin, Valérie; Nicolas, Guillaume
ABSTRACT In the field of biomechanics of quadrupedal locomotion in primates, infant‐carrying has received little attention. This study presents the first biomechanical study of infant‐carrying in captive female olive baboons (Papio anubis). We test whether females carrying infants conform 1) to the Support Polygon Model (Rollinson and Martin: Symp Zool Soc Lond 48 (1981) 377–427) of gait selection, according to which diagonality should decrease when the infant is carried cranially and increase when the infant is carried dorsally and caudally; 2) to Biewener's (Biewener: Science 245 (1989) 45–48) theory of limb postures, according to which females should extend their hind limbs more due to infant load, especially in the later stages when the infant is not fully autonomous but relatively heavy. This study focuses on the sagittal kinematics of quadrupedal gaits (joint angles and spatiotemporal parameters) of four females with and without infant loads at the CNRS Primatology Station (France). High‐speed video recordings were made using the technical platform "Motion Analysis of Primates" available in the animals' place of life. Regarding diagonality, our results do not fully conform to those predicted by the Support Polygon Model of gait selection; however, the model cannot be rejected at this stage in experiment. With regard to limb posture, our results do not support Biewener's (Biewener: Science 245 (1989) 45–48) theory: loaded females do not extend their hind limbs more as predicted; on the contrary, the hind limbs tend to be more flexed when the infant they carry is relatively heavy. Am J Phys Anthropol 155:392–404, 2014. © 2014 Wiley Periodicals, Inc.